PENGARUH AIR LINDI (LEACHATE) TERHADAP KUALITAS AIR PERMUKAAN DI SEKITAR TPA KOTA SORONG - Mierta Dwangga; Anif Farida (Universitas Lambung Mangkurat, 2023)
Waste has been a serious problem from the past until now. Waste contains pollutants both organic and inorganic. The waste decomposes naturally, but the results of the decomposition are scattered in the garbage pile. Piles of garbage produce a liquid called leachate. Such leachate water contains organic matter and heavy metals. Rainwater has a role as a solvent medium to carry pollutants from waste decomposition, if not managed properly pollutants in leachate water will pollute river water, air, growing pest animals and vector diseases so as to cause various environmental problems and negative impacts on health for those who use it around the Sorong City Landfill (TPA) location because leachate can enter and flow through soil pores and surface water in excessive amounts or concentrations. The purpose of this study was to determine the condition of surface water quality around the Sorong City Landfill (TPA) and identify the influence of leachate from the Sorong City Landfill (TPA) on the quality of surface water around the landfill with water samples taken, namely river water based on PP No. 82 of 2001 concerning Water Quality management and Water Pollution Control and KEPMEN LH No.51 of 1995 concerning Liquid Waste Quality Standards. The benefits of this research include being able to determine the quality of surface water around the Sorong City Landfill (TPA), as information material for residents living around the Sorong City landfill who use the water such as river water, as a basis for the arrangement of landfills (TPA) and the management of leachate wastewater treatment plants (WWTP) so that they are not directly discharged into the environment. In addition, this research is expected to be able to answer problems using methods that have been selected based on studies from previous research or research.